Analysis of leisure tourism in Peru during the COVID-19 pandemic - Mauricio, Ingrid; Mejia, Christian R.; Salinas, Omar; Solano, Sofia; Vicente-Ramos, Wagner (Business: Theory and Practice, 2022)
This study analyzes the economic impact caused by the COVID-19 pandemic on leisure tourism in Peru, in terms of tourist services such as means of transportation, accommodation, city tours and restaurants. The analysis is based on the application of a survey. The cross-sectional analytical study evaluated 2,443 potential tourists of legal age from the 25 regions of Peru who intended to engage in leisure tourism during the quarantine period. Likewise, potential tourists who intended to make a trip culminating the quarantine (in the remaining time of the year 2020) were evaluated. Based on the study of people who were going to carry out local leisure tourism until the end of 2020, the estimated losses in tourist services amounted to approximately 203 dollars millions (based on a budget less than or equal to 83.00, the amount that most respondents were willing to pay for tourist services). An increase in the demand for domestic leisure tourism is expected associated with the reduction in prices of each tourist service in order to reactivate this sector economically.